OPTIMALISASI LAYANAN KESEHATAN PRIMER MELALUI TRANSFORMASI DIGITAL: PENGEMBANGAN DAN EVALUASI SISTEM INFORMASI RAWAT JALAN PADA KLINIK GRIYA SARAS BRUNO - Damayanti, Alvina (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2026)
Digital transformation in primary healthcare is essential for enhancing operational efficiency and the quality of patient care. Griya Saras Bruno Clinic currently faces challenges in outpatient data management due to manual processes, leading to information fragmentation and prolonged patient waiting times. This study aims to design, implement, and evaluate an integrated outpatient information system at Griya Saras Bruno Clinic to optimize clinical workflows. The research employed the System Development Life Cycle (SDLC) approach using the Waterfall model for system development. System evaluation was conducted through functional testing (Black-box testing) and user acceptance analysis using the Technology Acceptance Model (TAM) framework. The system implementation successfully integrated registration, clinical examination, and pharmacy units into a centralized database. Evaluation results indicate that the system significantly reduced patient administrative waiting times and minimized the risk of medical data redundancy. TAM analysis showed high levels of user acceptance, particularly in perceived usefulness and perceived ease of use. This information system not only improves operational efficiency but also strengthens clinical documentation accuracy, providing a foundation for enhanced patient safety in primary healthcare facilities.